Evaluation of the perforators of the anterior communicating artery (AComA) using routine cerebral 3D rotational angiography. (3rd November 2015) - Lescher, Stephanie; Zimmermann, Maja; Konczalla, Jürgen; Deller, Thomas; Porto, Luciana; Seifert, Volker; Berkefeld, Joachim
Abstract : Background: Damage to perforating branches of the anterior communicating artery (AComA) is a known complication of surgical or interventional treatment procedures for AComA aneurysm leading to neurologic deficits. In spite of the clinical relevance of these AComA branches, they have not been systematically analyzed using imaging techniques and most of our knowledge is based on post-mortem injection studies or neurosurgical reports. We therefore analyzed three-dimensional rotational angiography (3DRA) images of the AComA, and propose a first imaging definition of the microvascular structures surrounding the AComA. Methods: Reconstructed 3D data derived from standard-of-care rotational angiography acquisitions (5 s DSA) were retrospectively analyzed. 20 patients undergoing selective cerebral angiography and 3DRA for therapy assessment were included in our study. 3DRA datasets were reconstructed and displayed using the volume rendering technique (VRT). Additionally, multiplanar reformatted CT-like cross-sectional images (MPR) were used to evaluate the number, size, and origin of the perforators of the AComA. Results: Perforating branches of the AComA could be demonstrated in all cases with large interindividual variations in vessel visibility. MPRs appeared to be superior to total VRT volumes in the visualization of the perforating branches of the AComA. Conclusions: 3DRA can be used to visualize perforating branches of the AComA in vivo. Since damage to these perforators may result in neurologic deficits, visualization of these vessels prior to surgery or endovascular aneurysm treatment could help in the planning of therapeutic interventions. Further refinement of current imaging techniques will be necessary, however, to increase the reliability of small vessel angiography.